A Petri-net approach for firefighting force allocation analysis of fire emergency response with backups. (January 2023) - Zhou, Jianfeng; Reniers, Genserik; Cozzani, Valerio
Highlights: The optimal allocation of emergency forces in front-line emergency response departments is studied. The impact of emergency response on the time to failure of installations in the event of a fire accident is considered in the allocation. A timed colored hybrid Petri-net (TCHPN) approach is proposed to model the emergency response process and analyze the allocation of emergency response forces. A case study of the emergency response to a tank fire illustrates the proposed approach. Abstract: Fire is one of the main accident scenarios occurring in chemical and process plants, and it can lead to domino effects due to thermal radiation. Emergency response is necessary to prevent fire escalation, in addition to safety barriers. In major industrial fire accidents, backup is usually required in emergency response, due to the lack of emergency response capacity of a single emergency response department. A method addressing the optimal allocation of emergency response forces, specifically considering the front-line departments, is developed in the present study. The emergency response of the front-line departments can reduce the thermal radiation received by the equipment adjacent to the primary fire and thus prolong the time to failure of the equipment, such that the backups have more time to get to the fire scene. The allocation analysis of emergency response teams is carried out considering the dynamic ttf of an adjacent equipment item resulting from the change in time of the thermal radiation received. A timed colored hybrid Petri-net (TCHPN) approach is proposed to model the emergency response process. The probability of preventing fire escalation is obtained from the TCHPN model and the optimal allocation of firefighting forces is determined. A case study illustrates the proposed approach, two scenarios are compared and results show that if a request for backup can be issued immediately according to the fire state, fewer emergency forces can be deployed on the front line department, such as the reduction from 6 emergency response teams to 3 teams to maintain the success probability of 0.91. The influence of other factors such as the position of fire departments and the layout of tanks on the allocation of emergency forces is also discussed.